Predicting Suicidal Behaviors in Patients With Bipolar Disorder Based on Stressful Life Events, Emotion Regulation, and Coping Strategies - Hadeghfard, Zeinab; Rahmani, Mohammad Ali; Sadati, Seyedeh Zahra (KMAN Counseling & Psychology Nexus, 2026)
Bipolar disorder is one of the most important psychiatric disorders and is associated with a high prevalence of suicide. Irregular social rhythms may play an important role in the development of suicidal thoughts and behaviors among these patients. Therefore, the present study aimed to investigate the role of social rhythm in predicting suicidal behaviors among patients with bipolar disorder and the mediating roles of emotion regulation and coping strategies. This study employed a descriptive-correlational design using regression analysis. The statistical population consisted of patients with bipolar disorder in Tehran during 2025–2026. A total of 193 patients were selected through convenience sampling from Iran Psychiatric Hospital and Rasoul Akram Hospital. The participants completed the Stressful Life Events Questionnaire (1985), Emotion Regulation Questionnaire (Gross, 2003), Ways of Coping Questionnaire (1984), and Suicidal Behaviors Questionnaire (2002). The data were analyzed using regression analysis in SPSS version 25. The results indicated that stressful life events (β = −0.23, p = .001), cognitive reappraisal (β = −0.13, p = .036), suppression (β = −0.23, p = .001), escape–avoidance (β = 0.21, p = .001), and planful problem-solving strategies (β = −0.13, p = .040) significantly predicted suicidal behaviors among patients with bipolar disorder. Based on the findings, it is recommended that clinicians pay particular attention to reducing stressful factors and improving emotion regulation and coping strategies in treatment programs designed to prevent and ameliorate suicidal behaviors among patients with bipolar disorder.